Effect of Straw Fiber Modification Methods on Compatibility between Straw Fibers and Cement-Based Materials - Demin Jiang; Penghui An; Suping Cui; Shiguo Sun; Jingzong Zhang; Tianfu Tuo (Advances in Civil Engineering)
To improve the utilization of crop straws as a resource and the compatibility between straw fibers and cement-based materials, the hydration of modified straw fiber cement-based composite (SFCC) was studied. The structural characteristic of SFCC was investigated by FTIR, SEM, and XRD. The results show that the setting time of several modified straw fiber SFCC pastes was shorter than that of the unmodified straw fiber SFCC paste, and the best method of fiber modification to improve the setting time of the SFCC paste is Na2O·nSiO2 treatment. The recommended fiber modification method for improving the compatibility between straw fibers and cement-based materials is alkali modification, followed by pure acrylic emulsion modification and Na2O·nSiO2 modification. To improve the strength of SFCC, the straw fiber should be modified by alkali, followed by pure acrylic emulsion and Na2O·nSiO2 modification and the method of water modification is also recommended. The phase types and relative contents of crystalline hydration products mixed with the modified straw fiber SFCC are significantly higher than those of the unmodified fiber SFCC. The fiber treatment method that was most helpful to increase the structural density of hydrates of SFCC was alkali treatment and pure acrylic emulsion treatment, followed by Na2O·nSiO2 treatment.